El Real Instituto Industrial de Madrid (1850-1867): medios humanos y materiales - Cano Pavón, José Manuel (1998)
The Royal Industrial Institute of madrid was founded in 1850 with the character of a central school of industrial engineering. It replaced the Conservatory of Arts, the place were crafts had formerly been taught for several years. The teaching staff and materials of the Conservatory were transferred to the new centre. The Royal Institute was being slowly consolidated. It completed in a short time its teaching staff, consisting of about thirty teachers and assistants, some of which were formed in France and Belgium. The building where it was installed was insufficient, but its material goods were adequate, specially the physics and chemistry laboratories. It also disposed of an industry museum, which possesed prototypes of machines and plenty of natural product samples. Based on archived records, this paper discusses the staff and material resources of the royal Institute while this school was open, with the purpose of evaluate its scientific level.